RESPON SISWA TERHADAP BAHAN AJAR E-MODUL MATEMATIKA DALAM MATERI BANGUN RUANG SISI DATAR - Nely Salu Padang (Jurnal Penalaran dan Riset Matematika, 2024)
The purpose of this study is to show some student responses regarding mathematics materials in e-modules in the context of flat-sided space building materials. The responses are based on the standards for making mathematics materials which are divided into three categories, namely material, language, and interest. The method used in this research is using descriptive method with qualitative sampling. The subjects of this study were grade VIII students from one of the junior high schools in Mimika Regency. The data collection technique used in this study was a student response questionnaire. The data analysis technique used was Semantic Differentiation Scale. The results of student responses to mathematics e-modules on flat-sided space building material are in the excellent criteria or 90%.